Consequences and assessment of the amendment to the Act on the Employment of Temporary Agency Workers - Reda-Ciszewska, Anna (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The subject of the article is the analysis of the regulations in the field of temporary agency work. Introduction of the Act on the Employment of Temporary Agency Workers in 2003 showed that the law was ineffective in terms of protecting the temporary worker. In practice, doubts have arisen regarding the application of the maximum period of temporary agency work or assignment to temporary work on the basis of a civil law contract. In 2017, the provisions of the Temporary Agency Employment Act were amended and their aim was to remove the shortcomings of the Act. The author evaluates the solutions introduced by the amendment.